2008
DOI: 10.1371/journal.pone.0004093
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Exacerbates HIV-1 Tat-Induced Cytokine Production in Astrocytes through Convergent Effects on [Ca2+]i, NF-κB Trafficking and Transcription

Abstract: Astroglia are key cellular sites where opiate drug signals converge with the proinflammatory effects of HIV-1 Tat signals to exacerbate HIV encephalitis. Despite this understanding, the molecular sites of convergence driving opiate-accelerated neuropathogenesis have not been deciphered. We therefore explored potential points of interaction between the signaling pathways initiated by HIV-1 Tat and opioids in striatal astrocytes. Profiling studies screening 152 transcription factors indicated that the nuclear fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 60 publications
3
109
2
Order By: Relevance
“…In the present study, Tat Ϯ morphine elevated CCL2/MCP-1, CCL5/RANTES, and IL-6 in vivo after 48 hours (Figure 3). This parallels our previous findings in vitro 24,27 and suggests enhanced inflammatory tone may contribute to dendrite pathology. From a therapeutic standpoint, it is important to recognize that synaptic apoptosis and focal losses in dendritic structure and function are not necessarily a prelude to death and in fact may be reversible.…”
Section: Structural Changes In Dendrites Induced By Hiv-1 Tat ϯ Morphinesupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, Tat Ϯ morphine elevated CCL2/MCP-1, CCL5/RANTES, and IL-6 in vivo after 48 hours (Figure 3). This parallels our previous findings in vitro 24,27 and suggests enhanced inflammatory tone may contribute to dendrite pathology. From a therapeutic standpoint, it is important to recognize that synaptic apoptosis and focal losses in dendritic structure and function are not necessarily a prelude to death and in fact may be reversible.…”
Section: Structural Changes In Dendrites Induced By Hiv-1 Tat ϯ Morphinesupporting
confidence: 91%
“…24 -26 The present work was undertaken to extend previous results suggesting that HIV-1 Tat exposure might disrupt endogenous opioid and chemokine signaling. 10,24,27 Addi-tionally, we tested for subtle neuropathological changes that might be caused by HIV-1 Tat and opiate interactions since neuron death (terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling) was not observed in our previous study. 14 Wild-type and transgenic mice expressing HIV-1 Tat 1-86 regulated by a doxycycline (DOX) inducible, glial fibrillary acidic protein (GFAP) promoter were continuously treated with placebo, morphine, and/or naltrexone (s.c. implants) Ϯ DOX for 2, 7, or 10 days.…”
mentioning
confidence: 99%
“…Notably, NF-κB activation can also be modulated by G-protein-coupled receptors, such as the μ-opioid receptor, through a variety of upstream events including the cAMP/PKA/CREB, PI3K/Akt/IKK, and PLC/ PKC/IkK pathways [12,43] . Recent studies have shown that, in cultured astrocytes from mice, exposure to morphine plus HIV Tat is sufficient to activate NF-κB and cytokine production [44] . Based on a number of previous studies showing that NF-κB regulates the expression of TNF-α, IL-1β, and IL-6 in immune cells and investigating the effects of TNF-α and IL-1β on NF-κB activation in glial cells [45] , it has been postulated that a positive feedback loop exists between pro-inflammatory cytokine expression and NF-κB activation [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these data are not unambiguously clear. Thus, it was reported that NF-B activity in different cell types is either increased (Liu and Wong, 2005;El-Hage et al, 2008) or decreased (Wang et al, 2008;Börner et al, 2009b) in response to opioids. Therefore, we investigated in detail molecular mechanisms underlying the regulation of NF-B by morphine in neuronal cells.…”
Section: Introductionmentioning
confidence: 99%